Collective Agreement as Evidence with Binding Legal Force in Decision of Industrial Relations Court - Sari, Andari Yuriko; Santoso PN, Sugeng (Jambura Law Review, 2024)
A Collective Agreement, once registered and ratified at the Industrial Relations Court, should be regarded as authentic evidence possessing binding legal force for all parties, including judges. However, in various rulings from both the District Court and Supreme Court levels, the Collective Agreement has been consistently disregarded as evidence with enduring legal implications and enforceability on the involved parties. The central issue investigated in this research pertains to how judges perceive the Collective Agreement as evidence and the position it holds as binding evidence in the decisions of the Industrial Relations Court. This research employs a normative legal analysis approach (statute case) and conducts a case study by examining multiple industrial relations court decisions that have overlooked Collective Agreements as evidence with binding legal force. In contrast to several prior studies and writings conducted by other entities, which have primarily confined the role of the Collective Agreement to being binding on the parties and admissible as evidence in the Industrial Relations Court, this research scrutinizes the Collective Agreement, asserting that it should be established with unequivocal legal force for the involved parties, rendering it conclusive and precluding further legal actions. Nevertheless, in various Industrial Relations Court Decisions, these agreements are, in fact, overlooked and not treated as evidence with binding legal force, thereby introducing legal ambiguity for the parties involved. Additionally, despite the ideal scenario of the Collective Agreement being crafted as an authentic deed to ensure its binding nature, practical instances reveal instances where Collective Agreements are private deeds, each possessing distinct evidentiary powers.